The Role Of Cites Management Authorities On The Law Enforcement Process On Shark Finning Crimes In Indonesia - Rafika Rizky Aulia Rahman; Arie Afriansyah (Faculty of Law, University of Mataram, 2022)
Sharks are one of the animals that are included in the CITES Appendix list and occupy the top position in the food chain in marine ecosystems. But in reality, these animals are often becomes the main catch targets or by-catch targets. The practice of shark finning is one of the activities that refer to cutting only the fins of sharks and throwing the rest of the body (whether alive or dead) back into the sea. If the animals that are at the top of the food chain in the sea are exploited irresponsibly so that they are threatened with extinction, this will have an impact not only on the species itself but will also have to impact other species and damage the marine environment. The purpose of this article is to find out how the role of management authorities in law enforcement in the crime of shark finning in Indonesian waters. Thus the question in this article is, how law enforcement will be able to suppress shark finning activities that occur in Indonesian waters. The research method uses a descriptive qualitative approach and is supported by secondary data based on available literature to explore about shark finning crime. Research results show that the Ministry of Maritime and Fisheries as the Indonesian fish resource management authority has participated in the Task Force to eradicate illegal fishing under the rules of the Minister of Maritime and Fisheries of the Republic of Indonesia related to the standard operating procedures of the Law Enforcement Task Force to Eliminate Illegal Fishing as a specific criminal charge for the crime of shark finning as transnational crime. If activities are carried out in the waters of Indonesia, the charges for fines of sharks in the waters of Indonesia are under the jurisdiction of Indonesia as a sovereign state.